Straying : a novel - McCloskey, Molly, 1964- (Scribner, 2018)
"From "an extravagantly gifted writer who deserves to be widely read" (Rachel Cusk, The Telegraph), this intimate, quietly stunning novel tells the story of a young American expat who settles in Ireland in the late 1980s, marries, and lives through the consequences of an affair. Alice, a young American, arrives in the West of Ireland with no plans and no strong attachments--except to her beloved mother, who raised her on her own. Alice falls in love with an Irishman, marries him, and settles down in a place whose customs she struggles to understand. In the course of a single hot summer, she embarks on an affair that breaks her marriage and sets her life on a new course. Years later, after working in war zones around the world, and in the immediate aftermath of her mother's death, Alice finds herself back in Ireland and contemplating the forces that led her to put down roots and then tear them up again. What drew her to her husband, and what pulled her away? Was her husband strangely complicit in the affair? Was she always under surveillance by friends and neighbors who knew more than they let on? "Molly McCloskey is one of Ireland's finest writers" (Colum McCann) and Straying is at once a gripping account of passion and ambivalence and an exquisite rumination on the things that matter most: the definition of love, the value of family, and the meaning of home"--